2002
DOI: 10.1002/app.11490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the doses and nature of vegetable oil on carbon black/rubber interactions: Studies on castor oil and other vegetable oils

Abstract: ABSTRACT:The effects of additives in various vegetable oils on the physical, mechanical, and adhesion properties of carbon black/rubber compounds were studied. Various doses of castor oil and some other oils such as paraffin oil, vegetable oil 1, and cashew nut shell liquid (CNSL) at a fixed dose (1 phr) were used. With an increase in the castor oil content, the modulus, tear strength, and tensile strength increased, whereas the hardness and adhesive strength exhibited little variation up to 1 phr. Beyond 1 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 9 publications
(15 reference statements)
1
32
0
Order By: Relevance
“…Previous work reported an improvement in physical and mechanical properties of carbon black filled NR by castor oil. [11] However, there are a few reports on rubber compounds containing jatropha oil. The objective of the present work was to study the effect of total replacement of aromatic oil by vegetable oil for SBR compounding by focusing on the non-edible vegetable oils i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work reported an improvement in physical and mechanical properties of carbon black filled NR by castor oil. [11] However, there are a few reports on rubber compounds containing jatropha oil. The objective of the present work was to study the effect of total replacement of aromatic oil by vegetable oil for SBR compounding by focusing on the non-edible vegetable oils i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is the palm benzyl ester behaves as a cure activator. 22 The soybean and coconut benzyl esters also had shorter scorch and cure times than the aromatic oil, suggesting they are cure activators. It is noted that the activators used in the rubber formulations are generally high molecular weight monobasic acids, or mixtures of stearic, oleic, lauric, palmitic, and myristic acids.…”
Section: Solubility Parameters and Behavior Of Processing Oils In Rubmentioning
confidence: 97%
“…Both castor and vegetable oil enhanced the physical and the mechanical properties relative to saturated paraffin oil. 4 The chemical and physical properties of 10 naturally occurring oils (i.e., rubber seed, neem, dolma, soybean, alsi, kurunj, sesamum, mustard, ground nut, and castor oils), and six petroleum-based oils (i.e., aromatic oil, paraffinic oil, naphthenic oil, low polycyclic aromatics (PCA) oil, power oil TDAE-A, and power oil TDAE-B) were investigated in prior work. [8][9][10] It was found that the naturally occurring oils were suitable in rubber compounding with even lower PCA contents than the low PCA oils MES and TDAE.…”
Section: Introductionmentioning
confidence: 97%
“…The vulcanizates containing PCNSL showed good retention of tensile properties after ageing due to the post-curing reactions during the ageing period [23]. The effect of addition of paraffin oil, vegetable oil, castor oil, and CNSL to natural rubber compounds have been compared in terms of the mechanical properties and reported [24]. Polymerized CNSL has been recommended as a substitute for DOP, DBP for nitrile rubber and neoprene rubbers [25].…”
Section: Introductionmentioning
confidence: 99%